Seed storage behavior: a compendium - Hong, T.D.; Linington, S.; Ellis, R.H.; International Plant Genetic Resources Institute (1996)
This handbook provides an introduction to seed storage physiology for those responsible for plant genetic conservation and a selective summary of the literature on seed survival in storage, and thus on seed storage behaviour, for over 7000 species from 251 families. Part IA summarizes progress in our understanding of seed physiology in relation to seed storage for genetic conservation in the past 17 years since the publication of The Storage of Recalcitrant Seeds: Achievements and Possible Approaches by King and Roberts (1979), and particularly the various problems that may result in the misclassification of seed storage behaviour. Part IB provides a compendium of information on seed survival during storage and attempts to classify plant species into the several categories of seed storage behaviour. You can search the data on seed storage behavior